Bridging the Gap Between Theory and Practice in a B.A. Program in EFL - Julia Zoraida Posada Ortiz; Eliana Garzón Duarte (Asociación Colombiana de Profesores de Ingles, 2014)
This article describes the theoretical principles underlying the research component of the Bachelor's program of Basic Education with an Emphasis in English at a public university in Bogotá (Colombia), and an exercise of syllabus revision that served to link theory and practice through the research component of the program. The aim of the exercise was to reflect upon the syllabus and discuss how, from the different components of the program, student-teachers can understand research as the bridge to link what they learn in class and their practice in school contexts. A group of teachers revised the theoretical foundations as well as their practice in each cycle of the program, using the main tenets of critical pedagogy, teacher research, reflective teaching, and case study.